Remote Work in IT: Benefits, Challenges and Future Directions - Escorcer, Mariana Rodrigues da Silva; de Queiroz, Lucas Dias; Lima, Kennedy Oliveira; Passos, John Kauan Oliveira; Neiva, André Paz da Silva; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
This article examines the evolution and impact of remote work, with a focus on the Information Technology (IT) sector. Although remote work gained widespread attention during the COVID-19 pandemic, it has been practiced and evolved for decades, driven by technological advancements and shifts in organizational practices. The pandemic has accelerated and intensified its adoption, forcing companies and employees to quickly adjust. Currently, as the health crisis and its impacts are no longer in the focus, we are seeing a movement among several companies towards reverting to a hybrid or fully in-office work model. This article explores the history of remote work, its rapid expansion during the pandemic, and the associated benefits and challenges. Remote work brings flexibility, cost savings, and access to a global talent pool, but also introduces difficulties in communication, performance management, and social isolation. The future of remote work will be shaped by continued technological innovation, changing worker expectations, and the ongoing search for an improved work-life balance.